The COVID-19 Pandemic and its Influence on Sleep Quality: A Narrative Review of Prevalence, Correlates, and Implications - Radziwonka, Agnieszka; Wrochna, Bartłomiej Maciej; Olborska, Anna; Niezgoda, Ada; Kosiorek , Paweł; Stondzik, Gabriela; Garbacz, Anna Izabela; Majszyk, Tomasz Julian; Głuski , Jacek; Brzozowska, Agnieszka; et al. (Quality in Sport, 2026)
Introduction:The COVID-19 pandemic, has been a global stressor, disrupting daily routines and increasing psychological distress. A growing body of evidence indicates a rise in reports of sleep disorders among the population during this pandemic [1]. This narrative review synthesizes current literature to summarize the scale, risk factors, and health implications of pandemic-related sleep disturbances. Aim of the study:This article aims to analyze the prevalence and clinical impact of sleep disturbances during the COVID-19 pandemic, with particular focus on risk groups, contributing psychosocial factors, and associations with mental health. State of Knowledge:Meta-analyses confirm a high global prevalence of sleep problems during the pandemic, with pooled rates of sleep disturbances exceeding 30% in the general population [2]. These problems were significantly more pronounced in specific groups, including patient-facing healthcare workers [3], patients infected with Covid-19, and individuals with pre-existing psychiatric conditions [4]. Key contributing factors included pandemic-related stress, fragmentation of habitual daily patterns, and the onset of circadian system instability [5]. A strong relationship has been established between sleep disturbances and worsened mental health, particularly anxiety and depression [6]. Furthermore, sleep problems have emerged as a persistent symptom of Post-Acute Sequelae of SARS-CoV-2 infection (PASC, or Long COVID) [7]. Conclusion:Sleep disturbances represent an important public health crisis precipitated by the COVID-19 pandemic, manifesting as "coronasomnia". This review concludes that systematically addressing sleep health is crucial for post-pandemic sleep disturbances recovery, necessitating targeted public health strategies that integrate standardized screening in vulnerable populations, promotion of sleep hygiene, and the implementation of evidence-based interventions like cognitive-behavioral therapy for insomnia.